RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN HONORARIUM GURU DAN PEGAWAI YAYASAN NURUL HUDA KECAMATAN BATANG TUAKA - M Azmi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2015)
Yayasan Nurul Huda District of Batang Tuaka a Private Institutions engaged in providing education that has several levels that Government Elementary School, MTs and Madrasah Aliyah, in terms of the development of the education foundation Nurul Huda has a number of employees and the employee, while in the recording system of payroll honorarium employee and the employee is still using a simple computer system so that they can be found inconsistencies in the data because the data is stored separately, which at the end of the accounting period (month) to process payroll to its employees and employees and to report salaries as accountability to the leadership and to reporting. The process of recording and payroll calculation applied by the Foundation still manual and thus causing payroll process is often too late. It is therefore necessary to have a system that can help the performance of the administrative staff and treasurer in the distribution and recording of employee salaries and employee payroll Nurul Huda Foundation. In this study, the method used to perform system development is the method of SDLC (System Development Life cicle) so that the development can be carried out by structured. The purpose of this research is to design information systems payroll honorarium of teachers and employees in the Foundation Nurul Huda district Batang Tuaka, so as to provide convenience to the user to know the teacher and employee payroll data, facilitate financial section in mengolala payroll data Keywords: Payroll, honoraria, SDLC and Nurul Huda.